Parental time restrictions and the cost of children: insights from a survey among mothers - Melanie Borah; Andreas Knabe; Kevin Pahlke (The Journal of Economic Inequality, 2020)
An important aspect when analyzing economic inequality between households with children is time. At given monetary incomes, the material well-being of families may be very different depending on how much time parents have at their disposal. In this paper, we provide estimates of the subjectively perceived cost of children depending on the extent of parental time restrictions. Building on a study by Koulovatianos, Schröder and Schmidt (J. Bus. Econ. Stat. 27:42–51, 2009) that introduces a novel way of using subjective income evaluation data for such estimations, we conduct a refined version of the underlying survey, focusing on young women with children in Germany. Our study confirms that the perceived monetary cost of children is substantial and increases with parental nonmarket time restrictions. The experienced loss in material living standards associated with supplying time to the labor market is sizeable for families with children.
Keywords: 300; Child cost; Equivalence scales; Full-time employment; Subjective income evaluations